2023
DOI: 10.21009/jbmk.0401.16
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Memengaruhi Intention to Stay pada Perusahaan Swasta di Jakarta

Abstract: ABSTRACT Private employees should intend to stay in their company for a long time. The intention to stay is related to many factors, including job satisfaction, work-life balance, and organizational commitment. This study aims to determine the effect of job satisfaction, work-life balance, and organizational commitment on the intention to stay of employees. The research subjects were 200 employees who worked at a private company in Jakarta. The research design used is the AMOS SEM method with a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Employee commitment, according to Agus and Selvaraj (2020), has a positive influence on the intention to stay. In contrast to the findings of Krismonika and Dwiatmadja (2020) and Saraswati et al (2023), who found no evidence of a partial relationship between organizational commitment and intention to stay.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Employee commitment, according to Agus and Selvaraj (2020), has a positive influence on the intention to stay. In contrast to the findings of Krismonika and Dwiatmadja (2020) and Saraswati et al (2023), who found no evidence of a partial relationship between organizational commitment and intention to stay.…”
Section: Introductioncontrasting
confidence: 99%
“…In line with Paré & Tremblay's (2007) research conducted on 394 Quebec members of the Canadian Information Processing Society, it failed and showed that organizational commitment has no influence on the intention to stay. The results of this study are in line with the results of research conducted by Krismonika & Dwiatmadja (2020) and Saraswati et al (2023), which show that there is no partial influence between organizational commitment and intention to stay.…”
Section: Hypothesis Testsupporting
confidence: 89%